Volatile flavor characteristics of scallops (Chlamys farreri) with different drying methods were analyzed based on GC-IMS and GC-O-QTOF - Pengfei Jiang; Xiaoqing Miao; Jing Li; Hang Qi; Shan Shang; Xiuping Dong (Food Chemistry: X)
To investigate the effects of different drying methods on the flavor of scallops, headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) combined with gas chromatography-olfactometry-quadrupole time-of-flight (GC-O-QTOF) was used to analyze the flavor of scallops processed by five drying methods. A total of 62 volatile organic compounds (VOCs) were identified by GC-IMS. 27 characteristic aroma compounds were identified by GC-O-QTOF, and the highest content was trimethylamine. 17 aroma compounds with GC-O ≥ 6 were screened by the time-intensity method, and the maximum aroma intensity value of 2-acetyl-1-pyrroline was 9.9 aroma compounds with relative odor activity value (ROAV) ≥ 1 were identified. Using GC-O ≥ 6 and ROAV ≥1 as the criteria, 6 differential aroma compounds were further screened, and the results proved that naturally dried scallops had a heavier fishy odor. These findings will provide deeper insights into the processing of scallops.